SWIFT, THOREAU, AND INNIS: SPACE, TIME, AND TECHNOLOGICAL INNOVATION IN COMMUNICATIONS - Briston, Michael (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1983)
Michael Bristol takes up the theme of ends and means in communications, and invites us to look retrospectively rather than prophetically, and with "critical respect", at the way in which resistance to technological pressures has been most ably expressed in the past. Swift’s satire, of the wondrous Lagadan machine whereby "the most ignorant Person at a reasonable Charge... may write books... without the least Assistance from Genius or Study," was aimed at "a kind of intellectual vanity (that proposes) replacing the more ambiguous forms of natural language... by a mathematically precise and unequivocal information system." Citing Thoreau at sorne length as well, and the modern Harold Innis, he outlines for us a range of thoughtful responses to the pressures exercised by space-binding and time-binding technologies on human resources and human creativity - pressures that have been with us for a long time. RÉSUMÉ Michael Bristol choisit le thème de la fin et des moyens dans le domaine de la communication pour nous inviter à jeter un regard rétrospectif plutôt que prophétique et d’émettre des critiques "respectueuses" sur la façon dont la résistance aux pressions technologiques s’est le mieux exprimée dans le passé. La satire de Swift sur la merveilleuse machine de Lagudan dans laquelle "la personne la plus ignorante est capable, moyennant une compensation raisonnable, de rédiger des livres ... sans l’aide du génie ou des études", visait une "sorte de vanité intellectuelle remplaçant les formes les plus ambigues du langage naturel ... par un système d’information ayant une precision mathématique et sans équivoque. Il citant également Thoreau et l’écrivain moderne Harold Innis, Bristol nous propose une gamme de réponses raisonnées aux pressions exercées par les technologies sur les ressources et la créativité humaine, pressions que nous subissons depuis très longtemps.